Core Loss Modeling for Permanent-Magnet Motor Based on Flux Variation Locus and Finite-Element Method - Huang, Yunkai; Dong, Jianning; Zhu, Jianguo; Guo, Youguang (IEEE transactions on magnetics, 2012)
Core-loss prediction is an important issue in design and analysis of permanent-magnet (PM) motors. Because of the diverse structure, flux distribution, and rotational variation of flux, it is difficult to predict the core loss in a machine exactly. In this paper, a core-loss model for the PM motor is introduced in which flux variation loci in different parts of the motor are predicted by carrying out a finite-element transient analysis. Since the flux variation pattern is complicated, an improved equation based on the conventional three-term expression is used for core-loss calculation. The core-loss model is developed totally in ANSYS parametric design language as a parametric model and it can be used easily for different types of PM motors. Calculation and experiments on a high-speed PM motor have shown that the model can produce results that agree with the experimental ones.